Pengaruh Kredibilitas JKT48 sebagai Brand Ambassador terhadap Keputusan Pembelian Erigo Apparel oleh Followers Instagram @fjkt48.bdg - Paskah Marpaung; Atwar Bajari; Ditha Prasanti (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The use of brand ambassadors has become increasingly prevalent among various brands, including Erigo Apparel. JKT48 was selected as a brand ambassador due to its strong influence on public opinion through its popularity on social media. However, there remains a lack of studies that specifically explore how the credibility aspects of JKT48 contribute to individual decision-making when choosing a product. This study aims to examine the influence of JKT48’s credibility dimensions, trustworthiness, expertise, and attractiveness on the purchase decisions of Erigo Apparel among followers of the Instagram account @fjkt48.bdg. The research is grounded in the source credibility theory proposed by Ohanian (1990). A quantitative approach was employed, using a survey method with 80 respondents selected through an f-test calculation using G*Power. The data were analyzed using SEM-PLS with the assistance of SmartPLS 4 software. The results indicate that all three credibility dimensions of JKT48 have a positive and significant effect on purchase decisions. Trustworthiness emerged as the most dominant factor, with a path coefficient value of 0.338 (t-statistic = 3.582; p-value = 0.000). All indicators in the model were declared valid and reliable, with an R-square value of 0.679, indicating that the model can substantially explain the purchase decision variable. These findings reinforce the idea that perceptions of JKT48’s credibility play a crucial role in shaping consumer purchase decisions.